P4.59 Online versus in-person testing: a qualitative analysis of testing preferences among youth and men who have sex with men using an online hiv/sti testing service in vancouver, canada. (8th July 2017) - Gilbert, Mark; Thomson, Kimberly; Chabot, Cathy; Haag, Devon; Shoveller, Jean
Abstract : Introduction: Youth and men who have sex with men (MSM) are two priority populations with regards to sexual risk, HIV/STI prevalence, and barriers to sexual healthcare. In 2014, an online HIV/STI testing service called GetCheckedOnline (GCO) was implemented in Vancouver, Canada to address several barriers to testing. We investigated the acceptability and perceptions of GCO among youth and MSM, and identified how various social positions related to age, sexual identity, and geography affected preferences for online versus in-person testing. Methods: We conducted in-depth, semi-structured interviews with 12 youth (ages 23–29) and 19 MSM (ages 30–71) who had used GCO at least once. Interviews were analysed for emergent themes and participants' sociodemographic data were collected via a brief questionnaire. Results: Youth participants identified predominantly as male (92%), Caucasian (58%), and heterosexual (50%). MSM participants identified as male (100%); Caucasian (84%); and gay, bisexual, or pansexual (68%, 26%, 5%). Both populations were motivated to use online testing for: convenience, not having to wait to get tested at a clinic, increased privacy/anonymity, and avoiding judgment from healthcare providers. Additionally, youth perceived online testing as modern and "the future." MSM participants perceived GCO as providing increased control over tests ordered and decreased anxiety due to receiving results faster. For three rurally-based MSM, GCO offered a way to test discreetly without identifying one's sexual orientation to a healthcare provider. Even among participants who reported routinely accessing face-to-face health services (including for health concerns other than STIs), GCO was described by most interviewees as advantageous in terms of convenience and privacy. Overall, 83% of youth and 84% of MSM said they would use GCO again. Conclusion: GCO was regarded as an acceptable and preferred option for accessing testing. Convenience was the most common reason for wanting to test online, although this varied somewhat by age, sexual orientation, and geography.